Inequality in Vietnamese Urban–Rural Living Standards, 1993–2006. (12th June 2013) - Thu Le, Huong; Booth, Alison L.
<x xml:space="preserve">Abstract</x> We investigate urban–rural inequality in Vietnam using data from the Vietnam Living Standard Surveys between 1993 and 2006. We find that mean per capita expenditure of urban households is consistently twice as much as that of rural households and that the urban–rural gap monotonically increases from the poorer to the richer groups of the expenditure distribution. To isolate factors contributing to the urban–rural gap, we apply the Oaxaca–Blinder type decomposition to a newly developed unconditional quantile regression method. Factors contributing significantly to the high urban–rural gap include inter‐group differences in education, household age structure, labor market activity, geographic location and their related returns, with education playing the most important role. Over the period, consistent with the country's massive rural–urban migration, we find that domestic remittance plays a significant role in shortening the urban–rural expenditure gap in the later years, 2002 and 2006.